Outcome of Rotation Flap Combined with Incisional Negative Pressure Wound Therapy for Plantar Diabetic Foot Ulcers - Jiajun Feng; Coeway Boulder Thng; Jason Wong; Quah Mei Fern Alison; Nicole Tao Ying Lim; Francis Keng Lin Wong; Kimberley Leow; Leon Timothy Charles Alvis; Sum Leong; Farah Gillan Irani; Wenxian Png; Eric Wei Liang Cher; et al. (Archives of Plastic Surgery)
Background Diabetic foot ulcers (DFUs) affect approximately 20% of diabetic patients and pose significant risks, especially for plantar wounds that bear weight. Conventional treatments often have suboptimal results, necessitating the exploration of reconstructive options. Plastic surgery interventions, such as skin grafts and flaps, have shown promising outcomes, but with considerable complications. This study evaluates the efficacy of rotation flap reconstruction with incisional negative pressure wound therapy (NPWT) for plantar DFUs.